1991
DOI: 10.1029/91jb00573
|View full text |Cite
|
Sign up to set email alerts
|

Thermal alteration of the magnetic mineralogy in ferruginous rocks

Abstract: The Northampton ironstone contains the paramagnetic minerals siderite and berthierine and a trace of the ferrimagnetic mineral magnetite. The magnetic fabric of this sedimentary rock, as defined by the anisotropy of magnetic susceptibility, is controlled by bedding compaction but is inverse (i.e., the maximum susceptibility axes are normal to the bedding plane). This inverse fabric is attributed to the dominating presence of siderite. The rocks were incrementally heated to 600°C, and the magnetic fabric was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 17 publications
3
43
0
Order By: Relevance
“…The values of χ FD % in the mineralized sample of 2-14 nm magnetite nanoparticles and Mössbauer spectroscopy identified a significant proportion of SP particles. The results of a magnetic susceptibility versus temperature experiment of the 2-14 nm sample that was repeated in rapid succession suggest the formation of new magnetite nanoparticles, which is similar to the results obtained by Hirt and Gehring (1991).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The values of χ FD % in the mineralized sample of 2-14 nm magnetite nanoparticles and Mössbauer spectroscopy identified a significant proportion of SP particles. The results of a magnetic susceptibility versus temperature experiment of the 2-14 nm sample that was repeated in rapid succession suggest the formation of new magnetite nanoparticles, which is similar to the results obtained by Hirt and Gehring (1991).…”
Section: Introductionsupporting
confidence: 74%
“…Berthierine is typically paramagnetic at room temperature. Hirt and Gehring (1991) found that magnetite is created in heating experiments, and this certainly occurred during a number of hydrothermal processes in our study area. This occurrence can explain the Mössbauer spectrum obtained in our case, which is the emerging of a ferromagnetic phase.…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…Some are SEDEX in origin (Damyanov and Vassileva, 2001;Xu and Veblen, 1996;Kimberley, 1989;Curtis andSpears, 1968 Wiewiora et al, 1998), other sulfide massive volcanogenic (Slack et al, 1992), metamorphic origin (Wybrecht et al, 1985), and associated to bauxite and laterite (White et al, 1985;Toth and Fritz, 1997). These minerals also occur in Northampton ironstone (Hirt and Gehring, 1991), in paleosol near Waterval Onder, South Africa (Retallack, 1986), in the oolitic ironstone beds, Hazara, Lesser Himalayan Copyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB. thrust zone (Yoshida, 1998), in metamorphic rock in the Sierra Albarrana pegmatite body (Del Mar Abad-Ortega and Nieto, 1995), in the coal-swamp deposits in Paleogene and Upper Triassic coal, Japan (Iijima and Matsumoto, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Hus [1990] found that room temperature oxidation of siderite created hematite, which acquired a fieldcontrolled, very stable crystalline remanent magnetization and concluded that siderite heated in air did not show magnetic interactions between the dissociation products hematite and maghemite. Hirt and Gehring [1991] studied the low-temperature bulk susceptibility and isothermal remanent magnetization (IRM) of the Northampton ironstone and concluded that siderite-rich samples were mineralogically stable in air over years, in contrast to Ellwood e! al.…”
Section: Introductionmentioning
confidence: 99%